Xanthohumol Inhibits TGF-β1-Induced Cardiac Fibroblasts Activation via Mediating PTEN/Akt/mTOR Signaling Pathway - Jiang C; Xie N; Sun T; Ma W; Zhang B; Li W (Dove Medical Press, 2020)
Chuanhao Jiang,1,2,* Ning Xie,3,* Taoli Sun,4 Wanjun Ma,2 Bikui Zhang,2 Wenqun Li2 1Department of Laboratory Medicine, The Second Xiangya Hospital, Central South University, Changsha, Hunan 410011, People’s Republic of China; 2Department of Pharmacy, The Second Xiangya Hospital, Central South University, Changsha 410011, People’s Republic of China; 3Department of Breast Cancer Medical Oncology, Hunan Cancer Hospital, The Affiliated Cancer Hospital of Xiangya Medical School, Central South University, Changsha, Hunan 410013, People’s Republic of China; 4Key Laboratory Breeding Base of Hu’nan Oriented Fundamental and Applied Research of Innovative Pharmaceutics, College of Pharmacy, Changsha Medical University, Changsha, Hunan 410219, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenqun Li Email liwq1204@csu.edu.cnBackground: Xanthohumol (Xn) is the most abundant prenylated flavonoid in Hops (Humulus lupulus L.), and exhibits a range of pharmacological activities. This study aimed to investigate the effect of Xn on TGF-β 1-induced cardiac fibroblasts activation and elucidate the underlying mechanism.Materials and Methods: The cellTiter 96® AQueous one solution cell proliferation assay kit was adopted to determine the cell viability of cardiac fibroblasts, and the proliferation was detected through 5-ethynyl-2ʹ-deoxyuridine (EdU) incorporation assay. The α-SMA protein expression was measured by using immunofluorescence and Western blotting. Western blotting was conducted to test the protein expressions of collagen I and III, PTEN, p-Akt, Akt, p-mTOR, mTOR, p-Smad3, Smad3 and GAPDH. The mRNA levels of α-SMA, collagen I and III were determined by quantitative real-time polymerase chain reaction (PCR).Results: Xn inhibited the TGF-β 1-induced proliferation, differentiation and collagen overproduction of cardiac fibroblasts. TGF-β 1 induced the down-regulated PTEN expression, Akt and mTOR phosphorylation. These effects of TGF-β 1 were suppressed by Xn, while blocking of PTEN reduced Xn-mediated inhibitory effect on cardiac fibroblasts activation induced by TGF-β 1.Conclusion: Xn inhibits TGF-β 1-induced cardiac fibroblasts activation via mediating PTEN/Akt/mTOR signaling pathway.Keywords: xanthohumol; Xn, cardiac fibrosis, cardiac fibroblasts, TGF-β 1, PTEN/AKT/mTOR pathway